Efektivitas Pelapisan Benih Dengan Polietilen Glikol (Peg) 6000 Dan Lama Penyimpanan Terhadap Viabilitas Benih Pepaya (Carica Papaya L.) Var. Merah Delima - Novita Hera; Dumaria Sahputri; Ahmad Taufiq Arminudin (LPPM Universitas Muhammadiyah Sumatera Barat, 2026)
ABSTRACT The availability of seeds of sufficient quality and quantity is a priority in expanding the area of the papaya Merah Delima to meet market demand which tends to increase. Seeds need to be stored so that they are available at all times and their viability needs to be maintained during storage. One effort that can be done is coating the seeds with polyethylene glycol (PEG) 6000. This research aimed to obtain the interaction, concentration of PEG 6000 and as well as the best storage period in maintaining seed viability papaya Merah Delima. This research was conducted in September to November 2023 at UARDS Screen House, Faculty of Agriculture and Animal Science, State Islamic University of Sultan Syarif Kasim Riau. The research was assigned in completely randomized factorial design and three replications. The first factor is the concentration of PEG 6000 levels: 0%, 10%, 20%, 30%, 40% and 50%. The second factor is the length of seed storage period levels: 6 months, 7 months and 8 months. The parameters used are seed water content, germination test, vigor index, fresh weight and dry weight of normal sprouts. The results of this study showed that the best interaction in the 30% PEG 6000 concentration treatment and 6 months storage resulted in germination test of 85.33%. The best concentration of PEG 6000 is a concentration of 30%, producing seed water content of 9,25%. The best storage period is 6 months of storage, producing seed water content of 9.86%. Seed coating with a 30% concentration of PEG 6000 and a storage period of 6 months can maintain the viability of papaya Merah Delima. Keywords: germination test, normal sprouts, seed quality, seed water content